Pertanggungjawaban Pidana terhadap Tindak Pidana Penculikan Anak oleh Orang Tua Kandung tanpa Hak Asuh - Revita Anggi Shelomita; Pepy Marwinata (Legalite : Jurnal Perundang Undangan dan Hukum Pidana Islam, 2026)
This research is conducted with the aim of analyzing the criminal liability of parents without custodial rights who abduct a child from the parent holding legal custody. The analysis considers whether the biological relationship between parents and children can eliminate criminal liability, as well as how the applicable legal provisions in Indonesia regulate such acts. This study employs a normative legal research method by examining primary and secondary legal materials, which are then systematically analyzed to obtain an understanding of the regulation and application of law regarding child abduction committed by parents without custodial rights. The results of the research indicate that although parents without custodial rights have a biological relationship with the child, if they abduct the child from the custodial parent, the perpetrators remain subject to criminal sanctions because their actions fulfill the elements of a criminal offense. This research also emphasizes the importance of ensuring the best interests of the child as well as legal certainty for parents who lawfully hold child custody.